The dark side of microbial processes: accumulation of nitrate during storage of surface water in the dark and the underlying mechanism - Kumar, Amit (2022)
In densely populated cities with limited land, storage of surface water in underground spaces is a potential solution to meet the rising demand of clean water. In addition, due to the imperative need of renewable solar energy and limited land resources, the deployment of floating solar photovoltaic (PV) systems over water has risen exponentially. In both scenarios, microbial communities in the water do not have access to sunlight. How the absence of sunlight influences microbial community function and the water quality is largely unknown. The objective of this study was to reveal microbial processes in surface water stored in the dark and water quality dynamics. Water from a freshwater reservoir was stored in the dark or light (control) for 6 months. Water quality was monitored at regular intervals. RNA sequencing was performed on the Illumina MiSeq platform and qPCR was used to substantiate the findings arising from the sequencing data. Our results showed that storage of surface water in the dark resulted in the accumulation of nitrate in the water. Storage in the dark promoted the decay of algal cells, increasing the amount of free nitrogen in the water. Most of the free nitrogen was eventually transformed into nitrate through microbial processes. RNA sequencing-based microbial community analyses and pure culture experiments using nitrifying bacteria Nitrosomonas europaea and Nitrobacter sp. revealed that the accumulation of nitrate in the dark was likely due to an increase in nitrification rate and a decrease in the assimilation rate of nitrate back into the biomass. IMPORTANCE Microbial communities play an essential role in maintaining a healthy aquatic ecosystem. For example, in surface water reservoirs, microorganisms produce oxygen, break down toxic contaminants and remove excess nitrogen. In densely populated cities with limited land, storing surface water in underground spaces and deploying floating solar photovoltaic (PV) systems over water are potential solutions to address water and energy sustainability challenges. In both scenarios, surface water is kept in the dark. In this work, we revealed how the absence of sunlight influences microbial community function and water quality. We showed that storage of surface water in the dark affected bacterial activities responsible for nitrogen transformation, resulting in the accumulation of nitrate in the water. Our findings highlight the importance of monitoring nitrate closely if raw surface water is to be stored in the dark and the potential need of downstream treatment to remove nitrate.